2019
DOI: 10.1159/000504963
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship of Dimensions of Maxillary Sinus Drainage System with Anatomical Variations and Sinusopathy: Cone-Beam Computed Tomography Findings

Abstract: Objective: The aim of this study was to evaluate the correlation between the length of the infundibulum and ostium height with the anatomic variations of osteomeatal complex (OMC) and sinus pathology using cone-beam computed tomography (CBCT). Methods: CBCT images of 204 patients (408 maxillary sinuses) were evaluated retrospectively. The height of the ostium and the length of the infundibulum were measured. The presence of maxillary sinus pathology, nasal septal deviation, Haller cells, concha bullosa, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
2
32
2
Order By: Relevance
“…This finding was consistent with the study results of Serifoglu I et al, Altunay ZO et al Shobeiri et al [ 19 , 27 , 28 ]. On contrary a recent Turkish study reported a significantly high mean SDA among men compared to women [ 29 ].…”
Section: Discussionmentioning
confidence: 83%
“…This finding was consistent with the study results of Serifoglu I et al, Altunay ZO et al Shobeiri et al [ 19 , 27 , 28 ]. On contrary a recent Turkish study reported a significantly high mean SDA among men compared to women [ 29 ].…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, one study found no differences in EI length between men and women. 18 Although differences between gender have been observed in terms of maxillary sinus dimensions, EI and MSNO measurements are similar between gender. was associated with greater EI length (p<0.05).…”
Section: Comparison Of Ei and Msno Dimensions Between Sides Gender And Age Groupsmentioning
confidence: 93%
“…As anatomical risk factors for intraoperative complication, such as maxillary sinus membrane perforation, Testori et al reported sinus membrane thickness, the presence of sinus septa, palatonasal recess, and sinus contour [ 6 ], while Akay et al [ 7 ] and Lee et al [ 8 ] reported on the relationship between sinus volume and the presence of septum and sinus membrane thickness. In another study, Testori et al reported that sinus membrane thickness, nasal septal deviation (NSD), previous history of sinusitis, and natural ostium obstruction were anatomical risk factors for postoperative maxillary sinusitis, while the anatomical structure of the maxillary sinus is known to affect intraoperative and postoperative complications [ 9 ].…”
Section: Introductionmentioning
confidence: 99%